Humanitarian Diplomacy in Southeast Asia: ASEAN’s Strategies in Addressing the Thailand-Cambodia Border Crisis Impact - Al Rasyid, Muhammad Aras; Husein, Rachmawati (Educational Leadership and Management Journal, 2026)
This study examines ASEAN's role in responding to the Thailand-Cambodia border crisis (2025-2026) through a humanitarian diplomacy approach amidst regional security dynamics. The primary focus is on strategies for mitigating humanitarian, political, and economic impacts, as well as the integration of digital technology and cross-border coordination. Using descriptive qualitative methods, data is sourced from official ASEAN Secretariat documents, AHA Centre technical reports, and related literature. The findings indicate that while humanitarian diplomacy was effective in defusing short-term tensions and coordinating aid through digital platforms, its overall effectiveness was hampered by disparities in political interests among member states. These barriers include a rigid adherence to the principle of non-intervention and unequal digital access, which slowed the response to the humanitarian crisis affecting hundreds of thousands of refugees. The study concludes that strengthening collective mediation mechanisms and digitizing preventive diplomacy are crucial for future regional stability.